Seroprevalence, attitudes and practices of the Baka Pygmies of eastern Cameroon towards HIV and AIDS - Essomba, Noel Emmanuel; Adiogo, Dieudonné; Koum, Danielle Kedy; Ndonnang, Carine; Ngo Ngwe, Madeleine Irma; Njock Ayuck, Léo; Lehman, Leopold; Coppieters, Yves (The Journal of Infection in Developing Countries, 2015)
Introduction: The vulnerable health status of Pygmies is the result of their continual exposure to the modern world. The purpose of this study was to determine the prevalence of HIV and the attitudes and practices of Baka populations towards HIV infection. Methodology: A descriptive and cross-sectional study was conducted over a five-month period in 12 Pygmy camps. A questionnaire was completed to collect information, and anonymous screenings were held. For screening, whole blood was collected. The Determine HIV-1/2 test was used as the rapid test, and the SD Bioline HIV-1/2 test was used as the second test. Associations between variables were checked. Results: A total of 560 Baka were recruited. The sex ratio was 0.92. Among the means of transmission, sexual intercourse was the most frequently cited (37.6%). A minority (28.5%) knew where to undergo an HIV test, 24.2% did not know that there exists treatment enabling patients to have a higher quality of life, and 75.7% had never used a condom. A total of 86.9% had never been tested for HIV. Subjects who had sex with the Bantu were three times more likely to be infected (p = 0.02), as well as those who had had more than three sexual partners. Conclusions: The changes affecting contemporary societies are inevitably influenced by the dominant factors of modernity, particularly progress, development, and social dynamics in all their aspects. Baka knowledge about HIV/AIDS is limited. Educational efforts, increased awareness, and guidance are needed.